ANALISA PENGELOLAAN PERMINTAAN DAN KAPASITAS PADA UMKM RnS DI KOTA BATAM - Fidia; Macnico, Peter; Christini, Julia; Sandra, Novi; Sembiring, Diamend Tino; Vivianti, Weni; Willam (Transpublika Publisher, 2022)
The RnS beauty salon is a business or service in the field of beauty that provides a variety of treatments. By carrying out various strategies in its marketing so that RnS Salon can be known by many people. This research uses descriptive analysis technique of primary data. The primary data was obtained from an interview with the owner of the RnS salon. The purpose of this study was to find out how RnS salons deal with these customer requests. This RnS is still not optimal in marketing because it only uses electronic media such as Facebook and Instagram and that's why most are not familiar with this RnS salon and reduce the pattern of demand for RnS salons. This RnS salon needs to be innovative in marketing that will be shown to consumers